Association between anterior open bite and pacifier sucking habit in schoolchildren in a city of southern Brazil - Tibolla,Claudiane (2012)
OBJECTIVE: The objective of this study was to verify from a school-based epidemiological survey, the prevalence of anterior open bite, analyzing the influence of pacifier habit in the school. METHODS: The first step was a questionnaire for the parents, and later clinical examinations in 237 school children, 3-14 years old, in the city of Santo Expedito do Sul/RS, Brazil. RESULTS: The population gender distribution was 50.3% boys and 49.4% girls with a mean age of 8.63 years, and 16% had primary dentition, 50.2% mixed dentition and 33.8 % permanent dentition. There was a 22.8% prevalence of anterior open bite, obtaining a significant association between anterior open bite and the pacifier sucking habit on the three dentitions. CONCLUSION: The duration and frequency of the habit were strongly associated with anterior open bite malocclusion in the deciduous and mixed dentitions.